Mapping global environmental suitability for Zika virus - Messina, Jane P.; Jänisch, Thomas (eLife, 2016)
A global map of environmental suitability for Zika virus and the estimated population living at potential risk can help refine public health guidelines, travel advisories and intervention strategies at a crucial time in the global emergence of this arbovirus.